THE EXTENT OFFICE TECHNOLOGY AND MANAGEMENT GRADUATES IN BAUCHI STATE POSSESS OFFICE APPLICATION SKILLS FOR MODERN OFFICE NEEDS (UNIZIK Journal of Educational Management and Policy, 2018)
The study ascertained the extent Office Technology and Management graduates in Bauchi State possess office application skills for modern office needs. One research question guided the study, while two hypotheses were tested at 0.05 level of significance. The study adopted descriptive survey research design. .The entire population of 119 supervisors in the banks, communication industries and ministries in Bauchi state were used for the study. Data were collected for the study with a 15- item validated questionnaire. Cronbach-alpha reliability test was used to determine the reliability of the instrument. Mean statistics was used to answer the research questions while standard deviation was used to check the spread of the responses to the mean. The null hypotheses were tested at 0.05 level of significance using independent t-test and Analysis of Variance (ANOVA).Findings of the study revealed that Office Technology and Management graduates possess office application skills to a moderate extent. However, supervisors in public and private organisations in Bauchi state differ significantly in their mean ratings on the extent OTM graduates possess office application skills for modern office needs. Conclusions were drawn and relevant recommendations were made which includes that graduates should use the period of National Youth Service to acquire practical knowledge in office application so as to prepare them for the labour market.